2022
DOI: 10.1371/journal.pone.0266467
|View full text |Cite
|
Sign up to set email alerts
|

Data augmentation using Variational Autoencoders for improvement of respiratory disease classification

Abstract: Computerized auscultation of lung sounds is gaining importance today with the availability of lung sounds and its potential in overcoming the limitations of traditional diagnosis methods for respiratory diseases. The publicly available ICBHI respiratory sounds database is severely imbalanced, making it difficult for a deep learning model to generalize and provide reliable results. This work aims to synthesize respiratory sounds of various categories using variants of Variational Autoencoders like Multilayer Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Such geometry-respecting representations are also observed in high-level brain areas such as prefrontal cortex and hippocampus [40, 41]. Developing this geometry-respecting representation is essential for semi-supervised learning [42, 43], few-shot learning [44], and data augmentation via imagination [44, 45]. Using VAE as a model of the visual system, we will study the computational advantage for low-resolution top-down generation ( Figure 1d ), and investigate the inspiration of this finding to advance the technique of sketch generation ( Figure 1e, f ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such geometry-respecting representations are also observed in high-level brain areas such as prefrontal cortex and hippocampus [40, 41]. Developing this geometry-respecting representation is essential for semi-supervised learning [42, 43], few-shot learning [44], and data augmentation via imagination [44, 45]. Using VAE as a model of the visual system, we will study the computational advantage for low-resolution top-down generation ( Figure 1d ), and investigate the inspiration of this finding to advance the technique of sketch generation ( Figure 1e, f ).…”
Section: Resultsmentioning
confidence: 99%
“…Such geometry-respecting representations are also observed in high-level brain areas such as prefrontal cortex and hippocampus [40, 41]. Developing this geometry-respecting representation is essential for semi-supervised learning [42, 43], few-shot learning [44], and data augmentation via imagination [44, 45].…”
Section: Resultsmentioning
confidence: 99%
“…For better generalization of moBRCA-net, we adopted a data augmentation based on the deep generative model to enlarge the training dataset size. Several recent papers have shown that conditional variational autoencoder (CVAE)-based data generation for certain minority classes in the imbalanced dataset improved the classification performance in various domain tasks such as respiratory disease classification [ 41 ], temporal pattern prediction based on electronic health records [ 42 ], and prediction of chemical structure based on the chemical properties [ 43 ]. We constructed a conditional variational autoencoder (CVAE) composed of two-layered encoder and decoder, which estimates the conditional distribution with latent variables and data, and generates samples for specified breast cancer subtype.…”
Section: Resultsmentioning
confidence: 99%
“…However, it creates new opportunities to develop COVID-19 screening tools for telemedicine and remote monitoring (Sharma et al 2022;Villa-Parra et al 2022). In future works, we will explore data augmentation techniques (Saldanha et al, 2022), transfer learning (Bhatt et al, 2021), and interpretable deep learning models (Joshi et al, 2021) to improve the interpretability and usability of our framework to help COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%